Small sweep - Ahmad Syafiq, Shiro (2009)
This report presents about the small sweep that had been fabricated with a new design, more efficiency and suitable to use in a mosque. Today, most of the small sweep is function by two hands. For a single hand user, it is not really friendly to them. The idea of the fabricating of this small sweep is based on student’s creativity. The materials selection in the fabricating process of this small sweep is a material with suitable weight, long life-span and can detain force depending on the function. Materials are proposed for the fabrication of the small sweep is aluminium, stainless steel and plastic. This report also focuses on the fabrication process of this small sweep.